The Application of Problem Based Learning (PBL) Methods To Improve Student Learning Outcomes - Rusdiyanto Rusdiyanto; Muhlisatul Mahmudh (Universitas Islam Jember, 2019)
Application is an action carried out both individually and groups with the aim of achieving the objectives that have been formulated. The problems examined in this study are research on improving the class VIII students mathematics results in a two-variable linear equation system through the application of the Problem Based Learning (PBL) method in MTs. Annidhom of Jember. The sample of this study was class VIII MTs. Jember Annidhom as many as 32 students. The method used in this study is observation, documentation, interviews, and test methods, while the data analysis uses the percentage formula of the results observations and the percentage of completeness of learning outcomes formula. Based on the results of the research in the first cycle obtained by students who completed learning as much as 24 or 72.22% of students and as many as 9 or 27.8% of students who didn't complete, while the mathematics learning outcomes of students in the second cycle that weren't completed were 2 or 6.06 % of students and completed as many as 31 or 93.93% of students, it is mean that the application can improve student mathematics learning outcomes. Keywords: problem based learning, learning outcomes